Enhancing Formal Academic Speaking through Problem-Based Learning in EFL Higher Education - Yaredi Waruwu (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2026)
Many EFL university students continue to experience difficulties in formal academic speaking, particularly in organizing ideas coherently and delivering presentations confidently, indicating a gap between general speaking ability and discourse-oriented communicative competence. This study aimed to investigate the effectiveness of Problem-Based Learning (PBL) in enhancing formal academic speaking performance among EFL university students. The study employed a quantitative quasi-experimental design using a non-equivalent control group involving two intact classes of fourth-semester students in an English Education program. The experimental group received instruction through Problem-Based Learning, whereas the control group was taught using a conventional teacher-centered method. Data were collected through pre-test and post-test oral presentations assessed using a standardized speaking rubric covering fluency, accuracy, pronunciation, vocabulary, coherence, and confidence. The data were analyzed using descriptive and inferential statistics, including independent samples t-tests, effect size analysis (Cohen's d), and gain score analysis. The findings revealed that the experimental group achieved significantly higher post-test scores than the control group (p < .001). The largest improvements were observed in coherence and confidence, indicating that PBL effectively supports students in organizing ideas systematically and delivering academic presentations more confidently. The findings suggest that PBL contributes not only to the improvement of academic speaking performance but also to the development of discourse competence and affective readiness in EFL learning. This study provides empirical evidence supporting the integration of Problem-Based Learning into EFL speaking instruction to enhance formal academic speaking competence in higher education.